1998
DOI: 10.1159/000007482
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Carcinoid with Histamine Production, Histamine Transporter and Expression of Somatostatin Receptors

Abstract: A case of sporadic, histamine-producing gastric carcinoid with liver metastases is reported. The patient was treated with somatostatin analogue (octreotide) combined with cortisone and blockade of histamine receptors prior to surgery, which included subtotal gastrectomy, excision of lymph node metastases and superficial liver metastases. Residual liver metastases were injected with ethanol. These interventions markedly reduced the urinary excretion of the main histamine metabolite (MeImAA). Eighteen months lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 23 publications
(38 reference statements)
2
24
0
Order By: Relevance
“…The positive assessment of endocrine differentiation of tumours requires the identification of general markers of neuroendocrine differentiation by immunohistochemistry (Bishop et al 1988). Widely used are cytosol markers such as neuron-specific enolase (NSE) (Bishop et al 1982) and protein gene product 9.5 (PGP 9.5) (Rode et al 1985), the membrane-bound neural cell adhesion molecules (NCAM) (Al-Khafaji et al 1998, Lantuejoul et al 1998, or granule markers such as chromogranin A and the ATP-dependent vesicular monoamine transporters 1 and 2 (VMAT1 and VMAT2) (associated with large, dense-core vesicles) (Lloyd & Wilson 1983, Rindi et al 1986, Erickson et al 1996, Kolby et al 1998, Eissele et al 1999, Rindi et al 2000 and synaptophysin (associated with small synaptic-like vesicles) (Jahn et al 1985, Wiedenmann & Franke 1985, Buffa et al 1988. The identification of specific tumour cell types requires hormone immunohistochemistry, searching first for hormones expressed by the DES cells of the anatomical district where the tumour is found and then for 'ectopic' hormones according to specific hyperfunctional syndromes (e.g.…”
Section: Diagnosismentioning
confidence: 99%
“…The positive assessment of endocrine differentiation of tumours requires the identification of general markers of neuroendocrine differentiation by immunohistochemistry (Bishop et al 1988). Widely used are cytosol markers such as neuron-specific enolase (NSE) (Bishop et al 1982) and protein gene product 9.5 (PGP 9.5) (Rode et al 1985), the membrane-bound neural cell adhesion molecules (NCAM) (Al-Khafaji et al 1998, Lantuejoul et al 1998, or granule markers such as chromogranin A and the ATP-dependent vesicular monoamine transporters 1 and 2 (VMAT1 and VMAT2) (associated with large, dense-core vesicles) (Lloyd & Wilson 1983, Rindi et al 1986, Erickson et al 1996, Kolby et al 1998, Eissele et al 1999, Rindi et al 2000 and synaptophysin (associated with small synaptic-like vesicles) (Jahn et al 1985, Wiedenmann & Franke 1985, Buffa et al 1988. The identification of specific tumour cell types requires hormone immunohistochemistry, searching first for hormones expressed by the DES cells of the anatomical district where the tumour is found and then for 'ectopic' hormones according to specific hyperfunctional syndromes (e.g.…”
Section: Diagnosismentioning
confidence: 99%
“…Very occasionally, (less than 1%), patients may complain of flushing and present with the 'atypical carcinoid syndrome' (7,8). Type 1 GCs occur more frequently in women in the fifth and seventh decades (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Histamine plays a major role in allergy, inflammation, and cardiovascular hemodynamics (13)(14)(15), and histamine and other factors released from carcinoid tumor are related to the clinical condition known as carcinoid syndrome (16,17). Recent studies have also suggested a potential role of histamine in the proliferation of some types of human tumor cells via auto/paracrine activity (18 -20).…”
mentioning
confidence: 99%